Biology in assisted reproduction. Introduction - Ascenzo Palacio, Alberto (2018)
The author has taken as the basis of this manuscript the content of the introduction to the Symposium on Assisted Fertility published in the Peruvian Journal of Gynecology and Obstetrics in 2012 (1). Infertility in Peru and in almost all countries is not considered an important disease to be taken into account as a public health problem (2). According to the National Institute of Statistics and Informatics (3), in Peru we should be around 201 170 000 people in 2018. Within the population growth, there should be 10 292 180 that were in the range of 20 to 39 years. According to the World Health Organization, 15% of them, that is to say 1 543 827, would present problems of infertility.